MARKET RESEARCH OF THE LÁZARO CÁRDENAS PROFESSIONAL UNIT (FOREIGN TRADE) - Téllez, Rogelio René Hernández; Téllez, Barbara Hernández (Editora Impacto Científico, 2025)
The document addresses market research at the Lázaro Cárdenas Professional Unit, specifically in the area of Foreign Trade. Market research in education aims to identify the needs, preferences, and trends of the sector, supporting decision-making, the design of educational offerings, and the launch of relevant products or services. Key areas include: Educational demand: analysis of the training needs of students, teachers, and institutions, interest in new methodologies, and the educational levels with the highest demand. Competition and existing offerings: evaluation of competing institutions and digital education platforms. Student/user profile: understanding the characteristics and expectations of those who participate in the educational process.DOI: https://doi.org/10.56238/edimpacto2025.069-004